2022
DOI: 10.1002/fsn3.2754
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and characterization of pectin extracted from banana and papaya mixed peels using response surface methodology

Abstract: A massive amount of fruit peels generated from fruit processing industries and household kitchens has resulted in nutritional loss and environmental problems. Pectin is a polysaccharide that is isolated from fruit peels and has been attributed to various applications. By proper waste management practices and the use of efficient methods for retrieval of pectin from fruit, peels would benefit from resource management. This study has aimed at the extraction of pectin from locally available fruit peels. Pectin ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…The FT-IR spectra of the pectin obtained from d-CPH with the organic acids with GRAS status are very similar to each other (Figure 4), and close to those reported for commercial pectin [9,44,52]. In FTIR spectra observed the -OH peaks at 3400-3200 cm −1 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The FT-IR spectra of the pectin obtained from d-CPH with the organic acids with GRAS status are very similar to each other (Figure 4), and close to those reported for commercial pectin [9,44,52]. In FTIR spectra observed the -OH peaks at 3400-3200 cm −1 .…”
Section: Discussionsupporting
confidence: 80%
“…Finally, the response surface methodology (RSM) is an experimental design and analysis tool aimed at finding the conditions for which one or several responses of an experiment are optimized [41,42] and has been used successfully in the optimization of numerous agro-industrial processes [43]. The extraction of pectin has not been an exception [36,[44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…The moisture content of the produced pectin using HCl as a solvent was found to be 12% which is the same as the standard specifications of pectin [32]. On the other hand, the ash content of pectin was found to be 2.2% which is less than the values obtained from the literature studies of 5.7%.…”
Section: Moisture and Ash Contentsupporting
confidence: 69%
“…When the Williamson equation was applied, lower values were reported ranging from 0.062 to 0.095 [33] for pectin extracted with ascorbic acid. All these results indicated that pectin showed a non-Newtonian flow and a pseudoplastic behavior [7,19,30,33,42,45] where the viscosity decreased with the increase of the shear stress [43] and pectin concentration [19,41]. Furthermore, Pryangini et al [33] reported values of the consistency factor k of 1.48 and 1.44 at 0.5 % and 2 % concentration [33].…”
Section: Application Of Cocoa Pods Pectin In Food Fieldmentioning
confidence: 99%
“…The amount and composition of neutral sugars have a great influence on their rheological properties and structure, because these provide hydroxyl groups that stabilize the gel and contribute to the formation of hydrogen bonds to immobilize free water [40]. Furthermore, protein from other sources is characterized by a lower content ranging from 1.1 to 7.2 % in sugar beet pulp [41] and banana and papaya mixed peels [42] using acid citric solutions 3 Application of Cocoa-Based Pectin in Food and Biomedical Applications…”
Section: Physicochemical Characteristics Of Pectin Extracted From Coc...mentioning
confidence: 99%